Required Treatment Expenditures for Hepatitis C Virus Infection and Advantage in the Reduction of Hepatocellular Carcinoma Incidence: Analysis of Possible Options in an Endemic Area - Joob, Beuy; Wiwanitkit, Viroj (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Hepatitis C virus (HCV) infection is a known underlying factor contributing to hepatocellular carcinogenesis. The use of direct-acting antiviral (DAA) medication is a form of clinical management for controlling HCV infection and reducing the hepatocellular carcinoma incidence. This medication is introduced to several endemic areas. The big concern is on the treatment expenditures. Several alternative options are proposed and it is required to assess the effect of each alternative option. Objective: Here, the authors assessed and estimated the required treatment expenditures for HCV infection and advantage in the reduction of hepatocellular carcinoma incidence based on the analysis of possible options in an endemic area. Methods: A medical economics analysis was done. Results: According to the cost–utility analysis, the best alternative option that is hereby recommended is DAA medication coverage for all cases. Conclusion: DAA medication coverage for all cases is recommended.
Keywords: Expenditure; hepatitis C; incidence; infection; treatment